2021
DOI: 10.1007/s40122-021-00273-w
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of CGRP-mAbs in Menstrual-Related Migraine: A Real-World Experience

Abstract: Introduction: Migraine shows a significantly higher prevalence in women, especially during reproductive age when menstrual-related hormonal fluctuations represent the most common migraine trigger. Indeed, over 50% of patients report a higher occurrence of migraine attacks during the perimenstrual window. Menstrual migraine attacks are consistently referred to as more disabling, less responsive to symptomatic treatments, longer in duration, and more prone to relapse than non-menstrual migraine attacks. Evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
(53 reference statements)
0
6
0
1
Order By: Relevance
“…However, the treatment of menstrual migraine still poses specific challenges, being a more resistant subtype that is less responsive to prophylactic pharmacological treatments [ 147 ]. Results of a recent study on the effect of CGRP(−receptor) monoclonal antibodies in 40 patients with menstrual-related migraine and three or more previous treatment failures further confirmed this [ 148 ]. Besides a significant reduction of median menstrual migraine frequency, pain intensity, and attack duration, they showed that menstrual migraine episodes had a slightly less treatment response compared to the non-menstrual migraine episodes (72.4% reduction vs. 60% reduction) [ 148 ].…”
Section: Expert Opinionmentioning
confidence: 65%
“…However, the treatment of menstrual migraine still poses specific challenges, being a more resistant subtype that is less responsive to prophylactic pharmacological treatments [ 147 ]. Results of a recent study on the effect of CGRP(−receptor) monoclonal antibodies in 40 patients with menstrual-related migraine and three or more previous treatment failures further confirmed this [ 148 ]. Besides a significant reduction of median menstrual migraine frequency, pain intensity, and attack duration, they showed that menstrual migraine episodes had a slightly less treatment response compared to the non-menstrual migraine episodes (72.4% reduction vs. 60% reduction) [ 148 ].…”
Section: Expert Opinionmentioning
confidence: 65%
“…A post hoc analysis of data from a phase 3 randomized trial indicated that erenumab reduced monthly migraine headache days compared with placebo in women with a history of menstrual migraine; however, unlike our study, the analysis did not specifically investigate migraine headaches occurring during menstrual periods separately from migraine headaches occurring outside of the 5-day perimenstrual window [ 34 ]. A real-world observational study conducted at a single center in Italy reported that CGRP/CGRP receptor antibodies, including galcanezumab, reduced the frequency, intensity, and duration of menstrual-related migraines occurring during the 5-day perimenstrual window in 40 women with ≥ three previous treatment failures [ 35 ]. Together, these results suggest that galcanezumab may be an effective preventive treatment for women experiencing migraine during menstrual periods.…”
Section: Discussionmentioning
confidence: 99%
“…Other preventive therapies include vitamin E, magnesium, and phytoestrogens. A recent study has also shown that administration of calcitonin gene‐related peptide (CGRP)‐associated antibodies once a month six times reduced the frequency, severity, and duration of menstruation‐associated migraine and improved response to analgesics [36].…”
Section: Migrainementioning
confidence: 99%